Photodeformable Liquid Crystalline Polymers Containing Functional Additives: Toward Photomanipulatable Intelligent Soft Systems. Issue 9 (14th September 2021) - Huang, Shuai; Huang, Yinliang; Li, Quan
Abstract : Liquid Crystalline Polymer Composites Diverse functional additives are incorporated into liquid crystalline polymers to enable them with excellent photo‐manipulatable deformability, which holds great potentials in developing smart soft actuators and robotic devices such as the light‐controlled conveyor belt. More details can be found in article number 2100038 by Shuai Huang, Yinliang Huang, and Quan Li.